Building change : architecture, politics and cultural agency - Findley, Lisa, 1955- (London ; New York : Routledge, 2005)
"Building Change provides a vision of a revitalized role for architecture as a critical cultural and spatial practice. It discusses the dynamic between power and building and lays out the spatial strategies those in power use to manipulate and control the physical world. These include segregation, marginalization, construction of hierarchies and the spatial transformations of mechanisms such as colonialism and globalization. The book goes on to investigate the shifting relationships among power, space and architecture in a world where a number of subjected people are reasserting their political and cultural agency. Lisa Findley argues that architecture, as a primary participant in the production of space, has an important role to play in supporting these changes. This question is how, within the scope of the design and making of buildings, can this be done?" "To explore this question, the book describes and analyzes four recent building projects embedded in complex and diverse historical, political, cultural and spatial circumstances: the Tjibaou Cultural Centre in New Caledonia; the Uluru-Kata Tjuta Cultural Centre in Australia; The Museum of Struggle in South Africa; and the Southern Poverty Law Center in the US."--BOOK JACKET.
Power, space and architecture -- Building future : Tjibaou Cultural Centre -- Building visibility : Ulur̲u-Kata Tjut̲a Cultural Centre -- Building memory : the Museum of Struggle -- Building presence : the Southern Poverty Law Center -- Architecture and change.
Includes bibliographical references (p. 214-222) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social change; Architecture, Modern -- 21st century; Architecture, Modern -- 20th century; Architecture -- Political aspects; Architecture and society; Electronic books